Optimizing Sustainable Tourism Routes through GIS to Enhance Tourist Length of Stay in Bukhara - Kilichov, Mukhriddin; Olsavsky, Frantisek; Baiburiev, Ruslan; Khayrullaeva, Nilufarbegim; Dávid, Lóránt Dénes (Journal of Cultural Analysis and Social Change, 2026)
Study analyzes the potential for extending the length of stay of tourists by optimizing tourism routes based on architectural heritage sites located in the Historic Center of Bukhara. Using GIS technologies (QGIS 3.40), the spatial distribution of 92 cultural heritage sites was examined and analyses such as K-means clustering, Shortest Path, and Service Area were conducted. For each cluster, optimal one-day walking routes were developed and the total walking distance and duration were calculated. Moreover, based on real statistical data from 2020-2024, the number of foreign tourist arrivals to Bukhara from 2025 to 2030 was forecasted using the ARIMA(0,0,0) model. The model results indicate that over 21.8 million tourists are expected to visit during this period. If the average length of stay is extended from 3 to 4 days, a further USD 83.33 in revenue may be generated per tourist. This could result in approximately USD 1.694 billion in additional income by 2030. The findings of the study serve as a foundation for strategic planning in developing sustainable cultural tourism in Bukhara, optimizing service infrastructure, efficiently managing tourist flows and ensuring the rational use of heritage sites. Outcomes also bring into line with the broader frameworks of circular tourism and the transition toward a circular society, where heritage resources are reused, community benefits are maximized, sustainability principles are reinforced.